2021
DOI: 10.1039/d1nr00790d
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica coated CeO2 nanozymes with combined lipid-lowering and antioxidant activity induce long-term improvement of the metabolic profile in obese Zucker rats

Abstract: Obesity is one of the most important public health problems that is associated to an array of metabolic disorders linked to cardiovascular disease, stroke, type 2 diabetes, and cancer. A...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
0
19
1
Order By: Relevance
“…Treated rats presented a lower body weight and reduced circulating levels of insulin, leptin, glucose, and triglycerides. In comparison, recent data from our lab [94] found lower circulating triglyceride levels in 14-week-old obese Zucker rats treated with CeO 2 NPS (0.1 mg/kg twice weekly in weeks 8 and 9; 4 nm) but did not find significant effects on the body weight or circulating levels of insulin and glucose. In addition, no significant effects of CeO 2 NPs on liver fat accumulation were observed by hepatic oil red staining or lipidomic analysis.…”
Section: Liver Steatosiscontrasting
confidence: 77%
“…Treated rats presented a lower body weight and reduced circulating levels of insulin, leptin, glucose, and triglycerides. In comparison, recent data from our lab [94] found lower circulating triglyceride levels in 14-week-old obese Zucker rats treated with CeO 2 NPS (0.1 mg/kg twice weekly in weeks 8 and 9; 4 nm) but did not find significant effects on the body weight or circulating levels of insulin and glucose. In addition, no significant effects of CeO 2 NPs on liver fat accumulation were observed by hepatic oil red staining or lipidomic analysis.…”
Section: Liver Steatosiscontrasting
confidence: 77%
“…Surface modification ranging from functional group, inorganic ions and small molecules to macromolecules has been revealed as a promising strategy to regulate the mimetic enzyme properties of metal-and metal oxide-based nanozymes by affecting their surface chemistry [247][248][249]. For instance, ligands such as glutathione (GSH), dendrimer, DNA, and protein tend to protect metal nanoclusters from aggregation, thence reinforcing the stability, biocompatibility and catalytic activity of nanozymes [250,251].…”
Section: Surface Modificationmentioning
confidence: 99%
“…Robert [ 20 ] has reported that the ultraviolet-visible (UV-Vis) spectra of CeO 2 -NPs core before and after mSiO 2 coating are similar, confirming that the initial CeO2-NPs coating was successful and NP aggregation or degradation not induced. Importantly, in contrast to uncoated CeO 2 -NPs, mSiO 2 coating allowed colloidal stability in physiological media.…”
Section: Resultsmentioning
confidence: 97%